ANALISIS DISKRIMINAN MARKETING MIX TERHADAP KEPUTUSAN PEMBELIAN HARIAN PAGI RADAR JEMBER - Sudaryanto, Sudaryanto; Setiawan, De Irman (BISMA: Jurnal Bisnis dan Manajemen, 2012)
This study aims to analyze the marketing mix variables (product,price, promotion, place, people, processes, and physical evidence) todifferentiate the consumer's decision to buy or not buy Harian Pagi RadarJember. More over, the study also analyze which marketing mix variables thatinfluence the most dominant of the consumer decision to buy or not buyHarian Pagi Radar Jember. The population in this study is the people who buyHarian Pagi Radar Jember and sample was selected based on purposiverandom sampling. Discriminant analysis results the are differences betweenconsumer’s want and do not want to buy Harian Pagi Radar Jember. Morespecifically amongthe marketing mix factors the most dominant influence onthe decision to buy or not buy the Harian Pagi Radar Jember, is a factorprocess that represented by the variable ordering media. The seconddominant factor is a people service that represented by the variable ofemployee’s knowledge.